Victims’ rights, international wrongs, and restorative justice: How to square the circle of accountability and redress for international crimes? - Reiter Axelle (Temida)
International law is increasingly focusing on criminal avenues to deal with past human rights abuses. In this frame, the role of victims is often marginalized, if not totally ignored, and they are sometimes further victimized. It is put forward that the problem lies largely in the punitive character of criminal law and its focus on prosecution. The paper explores the shortcomings of this approach and suggests possible solutions. Two promising alternatives are worth investigating. First, states’ liability can now be invoked for international offences, through other avenues than penal justice. Secondly, more individuated compensatory and restorative mechanisms, grounded in tort law, contract and restitution, sidestep the tensions underlined. Reliance on both states’ liability and traditional private law remedies presents the significant advantage of perfectly fitting in the human rights paradigm and repositioning the victims at the centre of the proceedings.